The Causal Evidence of Birth Weight and Female-Related Traits and Diseases: A Two-Sample Mendelian Randomization Analysis - He, Renke; Liu, Rui; Wu, Haiyan; Yu, Jiaen; Jiang, Zhaoying; Huang, Hefeng (Frontiers in Genetics, 2022)
Objectives: A large meta-analysis indicated a more pronounced association between lower birth weight (BW) and diseases in women, but less concern about the causality between BW and female-related phenotypes and diseases. Methods: Mendelian randomization (MR) analysis was used to estimate the causal relationship between two traits or diseases using summary datasets from genome-wide association studies (GWAS). Exposure instrumental variables (IVs) are variants that are strongly associated with traits and are tested using four different statistical methods, including the inverse variance weighting (IVW), MR-Egger, weighted median, and weighted mode in MR analysis. Sensitivity analysis and horizontal pleiotropy were assessed using leave-one-out and MR-PRESSO packages. Results: The body mass index (BMI) in adulthood was determined by the BW (corrected β = 0.071, p = 3.19E-03). Lower BW could decrease the adult sex-hormone-binding globulin (SHBG) level (β = −0.081, p = 2.08E-06), but resulted in increased levels of bioavailable testosterone (bio-T) (β = 0.105, p = 1.25E-05). A potential inverse effect was observed between BW and menarche (corrected β = -0.048, p = 4.75E-03), and no causal association was confirmed between BW and the risk of endometriosis, leiomyoma, and polycystic ovary syndrome. Conclusion: Our results suggest that BW may play an important role and has a significant direct influence on female BMI, SHBG and bio-T levels, and menarche.